No strong association between alleles of tumour necrosis factor alpha and interleukin-1 receptor antagonist and corneal melting associated with systemic vasculitis - McKibbin, M (2000)
AIMS—To investigate polymorphism within the tumour necrosis factor alpha (TNF-α) promoter region and within the interleukin-1 receptor antagonist (IL-1Ra) gene in a group of patients with vasculitis associated corneal melting. METHODS—The polymorphic regions at position -308 on the TNF-α promoter region and in intron 2 of the IL-1Ra gene were amplified by the polymerase chain reaction (PCR). The resultant products were separated by electrophoresis on agarose gels and visualised by ethidium bromide staining. Genotype and allele frequencies for the 20 patients were compared with healthy controls from the same geographical area. RESULTS—The allele frequencies in the patient and control groups respectively for the TNF-α and IL-1Ra sites studied were as follows: TNF1, 82.5% and 80.2%; TNF2, 17.5% and 19.8%; IL-1Ra*1, 82.5% and 78.3%; IL-1Ra*2, 15% and 20%; IL-1Ra*3 2.5% and 1.5%. Although there was a trend for the IL1Ra*2 allele to be more common in the control group, no allele was found to have a statistically significantly association with the patient group: TNF1 p = 0.89; TNF2 p = 0.89; IL-1Ra*1 p = 0.65; IL-1Ra*2 p = 0.68; IL-1Ra*3 p= 0.50. CONCLUSIONS—The results suggest that the polymorphic alleles of TNF-α and IL-1Ra studied play little or no part in the susceptibility to corneal melting among these patients with systemic vasculitis.